Effects of application rate on spray deposition, stink bug control, and yield in soybean crops - Santos, José L. C. [UNESP]; Raetano, Carlos G. [UNESP]; de Carvalho, Fernando K.; Ferreira-Filho, Pedro J.; Guerreiro, Júlio C.; Ferrari, Samuel [UNESP]; Nascimento, Vagner [UNESP]; Tomaz, Rafael S. [UNESP]; Argioli, Agatha S. [UNESP]; Prado, Evandro P. [UNESP] (Springer Nature, 2022)
Stink bugs are economically important pests in soybean crops, affecting yield as well as the physiological and sanitary quality of grains or seeds. The present study aimed to assess the spray deposition into soybean canopy, stink bug control, and soybean yield as affected by insecticide application rate. Field experiments were carried out evaluating the variations of 60, 110, 160 and 210 L ha−1 application rates in two seasons. The spray deposition on soybean leaves taken from the bottom, middle and top canopy sections was quantified using Brilliant Blue marker dye. The efficacy of the application rate treatments applied with insecticides was determined based on stink bug control and soybean yield. In general, the amount of spray deposit on soybean sections and plant canopy had little difference regardless of the spray volume. The control of stink bugs showed only a significant difference between the treatments that received insecticide when compared to the control treatment, regardless of the application rate. In two soybean seasons, yield was reduced by stink bug infestation in the control treatment.
Keywords: Insecticide spray rate; Pesticide application; Soybean crop yield; Spray deposits; Stink bug control